Enhancing Learning Outcomes through Kahoot! - Based Educational Games in Engine and Heavy Equipment Courses for Phase F Heavy Equipment Engineering Students - Enjela Dwi Ananda; Ambiyar; Mahesi Agni Zaus; Sadly Firmansyah (Jurnal Vokasi Teknik Informatika, 2025)
This study investigates the effect of the Kahoot! educational game on student learning outcomes in the Engine and Heavy Equipment Unit course for Phase F students at SMK Muhammadiyah 1 Pekanbaru. A quasi-experimental design with equivalent control and experimental groups (n=18 each) was employed. Data were analyzed using normality and homogeneity tests, confirming suitability for parametric testing. Hypothesis testing using an independent t-test revealed a significant improvement in the experimental group’s mean post-test score (80.3) compared to the control group (74.2), with t (34) = 3.618, p < 0.05. The pre-test scores showed no significant difference between groups, ensuring comparability. These findings demonstrate that Kahoot! as an interactive gamified learning tool effectively enhances student engagement and academic performance in vocational engineering education. This study contributes novel empirical evidence supporting the integration of gamification in technical skill development, addressing a research gap in vocational ICT-based pedagogy.